Block and Weddle Methods For Solving nth Order Linear Delay Fredholm Integro-Differential Equations (Journal of the College of Basic Education, 2022)
A proposed method is presented to solve nth order linear delay Fredholm integro-differential equations (DFIDE's) numerically using fourth-order six steps block and weddle methods. New algorithms with the aid of Matlab language are derived to treat numerically three types (retarded, neutral and mixed)